Valorization of saffron waste as a natural source of 3-hydroxy-γ-butyrolactone, a valuable chiral building block for pharmaceutical applications - M. Corti; S. Princiotto; M. Zuccolo; G. Beretta; S. Dallavalle; A. Pinto; F. Annunziata; G. Borgonovo (Tetrahedron Green Chem)
Saffron is the most expensive spice, appreciated in the best cuisine all over the world. However, its production is connected to the generation of a high volume of waste, i.e. stamens, leaves, tepals, spathes, corm, and tunics. Several biologically active compounds and high value chemical have been identified in the saffron biomass extracts, among which is found 3-hydroxy-γ-butyrolactone (3-HBL), a chiral building block involved in the production of different active pharmaceutical ingredients. The development of the first green and scalable extractive methodology for the isolation of 3-HBL from saffron tepals and stamen could be of great interest for different chemical sectors. After the selection of the best extractive medium (ethyl acetate) and the optimization of the operative procedure to a two-step protocol, microwave assisted extraction and accelerated solvent extraction were compared. The results showed a 3.6 ± 0.2 % vs 2.1 ± 0.1 % w/w recovery and could be exploitable not only on a lab scale but also for a possible industrial application. An enantiomeric excess of 14 % of the (S)-(−) isomer was found.